Lo Spirito, forza divina del creato - Niccacci, A. (Liber Annuus, 2000)
Abstract Spirit-rûa˙ is the force of life coming from God. It plays different functions: in the cosmos, in animals, in humanity and in God himself. As such, it generates a certain “con-naturalness”, or congruousness, among the different worlds — divine, animal, human, and the cosmos as a whole. There results a vision of reality that is biblical but reflects in a special way the wisdom movement. With the help of relevant biblical texts, the paper traces a quick overview of the different functions of the term rûa˙ in the Old Testament while leaving aside the functions of the Spirit of God in the prophets, the judges and the heroes of Israel, the king, and the Messiah, which are most frequently dealt with by scholars. It illustrates the Spirit in the cosmos, in the living creatures, in the human being; God’s Spirit in humanity, spirit of humanity; Spirit and flesh, Adam and Christ; Spirit and new creation; Spirit as hypostasis?; Spirit-rûa˙ for a theology of the feminine; Spirit and ecumenism. More and more, Rûa˙ is a term impossible to define exactly and at the same time able to take on ever new and superior connotations.